(untitled) (Research, Society and Development, 2022)
Objective: to develop and validate an educational technology for nutritional support in chronic wounds healing, as a therapeutic support strategy for the clinical practice of health professionals. Methodology: the research development had a prospective, transversal character, with an analytical quantitative approach, through content validation through a Likert-type scale using the Pasquali method, with the participation of 7 evaluators in the health area, with a minimum degree of specialists; at least two years of experience in the area related to the book prepared. For data evaluation, the content validity index (CVI) was adopted, and the requirement with a level > 0.78 was considered valid. Results: the book was validated by a multidisciplinary team (nutritionists, nurses, physician and physical therapist), with a global CVI of 0.99 and an overall approval percentage of 94.2%, classified by the experts. Final considerations: the findings of the study indicate that the educational technology on nutritional support in the healing of chronic wounds was validated by the expert judges participating in the evaluation process, allowing a great tool for application in care practice aimed at patient recovery.